2021
DOI: 10.3389/fenvs.2021.746090
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Impacts of Aerosols During COVID-19 Lockdown Period Over the Indian Region

Abstract: The COVID-19 lockdown restrictions influenced global atmospheric aerosols. We report aerosol variations over India using multiple remote sensing datasets [Moderate Resolution Imaging Spectroradiometer (MODIS), Ozone Monitoring Instrument (OMI), Cloud-Aerosol Lidar, and Infrared Pathfinder (CALIPSO)], and model reanalysis [Copernicus Atmosphere Monitoring Service (CAMS)] during the lockdown implemented during the COVID-19 pandemic outbreak period from March 25 to April 14, 2020. Our analysis shows that, during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 78 publications
4
13
0
Order By: Relevance
“…Several other recent studies have also documented considerable reduction in AOD levels (e.g. Kumar 2020 ; Singh and Chauhan 2020 ; Kumari and Toshniwal 2020 ; Bhawar et al 2021 ) Model-based analysis also documents reduced aerosol amount (particularly over southern and eastern Asia) and associated increase in surface shortwave radiation levels due to COVID-19 regulations (e.g. Jones et al 2021 ; Fadnavis et al 2021 ).…”
Section: Introductionmentioning
confidence: 87%
“…Several other recent studies have also documented considerable reduction in AOD levels (e.g. Kumar 2020 ; Singh and Chauhan 2020 ; Kumari and Toshniwal 2020 ; Bhawar et al 2021 ) Model-based analysis also documents reduced aerosol amount (particularly over southern and eastern Asia) and associated increase in surface shortwave radiation levels due to COVID-19 regulations (e.g. Jones et al 2021 ; Fadnavis et al 2021 ).…”
Section: Introductionmentioning
confidence: 87%
“…The wind system showed a major change in northern India and IGP during the first half of March bringing in the transition from winter to pre-monsoon. Also, Bhawar et al ( 2021 ) observed that the transport of dust from West Asia was lower compared to the previous years during the lockdown period, in spring of 2020. This led to the reduction of dust aerosols over the Indian region.…”
Section: Resultsmentioning
confidence: 97%
“…As a result, areas of the surface with the same optical properties can have different brightness. For calculations using the Bouguer's formula, it is necessary to know the optical thickness of the atmosphere τ [12][13]. This can be done by measuring the attenuation of solar radiation on Earth.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…From the satellite you can estimate the brightness of objects with a priori known optical characteristics. It is also possible to roughly estimate τ in the visible part of the spectrum using the relationship between τ and the meteorological characteristics of the troposphere -air temperature, wind speed, relative humidity and water vapor pressure [12][13]. Bradley M. and Gasseler M. [12] note that the influence of the atmosphere can be taken into account more accurately on the basis of the theory of radiation transfer in the atmosphere.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%